2009
DOI: 10.1152/ajpregu.00200.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sex defines the age dependence of endogenous ACTH-cortisol dose responsiveness

Abstract: Whether similar sex differences operate in humans is unknown. To test this notion, we estimated ACTH-cortisol dose-response properties analytically in 48 healthy adults (n ϭ 22 women, n ϭ 26 men), ages 18 -77 yr, body mass index (BMI) 18 -32 kg/m 2 , previously studied at two medical centers. Plasma ACTH and cortisol concentrations were measured every 10 min for 24 h. The 145 sample pairs were used in each subject to estimate ACTH-cortisol drive via a logistic function. Statistical analyses revealed that 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 83 publications
2
36
0
Order By: Relevance
“…Factors that have been demonstrated previously to affect cortisol values including gender, BMI and inhaled corticosteroid use did not influence the downward trend in peak cortisol responses in adolescence. Sexual dimorphism has been demonstrated previously with respect to cortisol production and metabolism in adolescents (30) and older adults (31,32). In our cohort, there was a non-significant tendency towards higher stimulated cortisol responses in females.…”
Section: Discussionsupporting
confidence: 63%
“…Factors that have been demonstrated previously to affect cortisol values including gender, BMI and inhaled corticosteroid use did not influence the downward trend in peak cortisol responses in adolescence. Sexual dimorphism has been demonstrated previously with respect to cortisol production and metabolism in adolescents (30) and older adults (31,32). In our cohort, there was a non-significant tendency towards higher stimulated cortisol responses in females.…”
Section: Discussionsupporting
confidence: 63%
“…Other studies have reported no such age effect [280,283]. Interestingly, a recent study reported that 24-h cortisol levels were lower in men and higher in women with age [284]. This was attributed to decreased ACTH efficacy with age in men and increased ACTH efficacy with age in women [284].…”
Section: Humansmentioning
confidence: 93%
“…Interestingly, a recent study reported that 24-h cortisol levels were lower in men and higher in women with age [284]. This was attributed to decreased ACTH efficacy with age in men and increased ACTH efficacy with age in women [284]. Shifts in the timing of circadian peaks at older ages with later [285] or earlier morning peaks have also been reported [282,283].…”
Section: Humansmentioning
confidence: 99%
“…Details of the dynamic dose-response methodology were described in several earlier papers (11,16,17,18,19). The goal here was to relate time-varying ACTH concentrations (input, effector) to time-varying cortisol secretion rates (output, response) via both a classic fourparameter logistic dose-response function and a fiveparameter logistic dose-response function that contain two potencies to accommodate allowable (possible, but not obligatory) downregulation of ACTH drive.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of ACTH secretion with that of cortisol suggested diminished responsiveness of the adrenal gland in obesity (10). A recent analytical method allows noninvasive estimation of physiological (nonlinear) dose-response functions from serially sampled hormone-effector response pairs, such as LH and testosterone, or ACTH and cortisol, without injection of hormone agonists, antagonists, or labeled compounds (11). Relevant hormone pairing (i.e.…”
Section: Introductionmentioning
confidence: 99%